Peran Orang Tua dalam Meningkatkan Minat Membaca Anak Usia Sekolah Dasar - Futri Aysah; Lu'luil Maknun (Dawuh Guru: Jurnal Pendidikan MI/SD, 2023)
This study aims to determine the role and attention of parents to increase children's interest in reading and the obstacles experienced. This research uses descriptive qualitative. The subjects of this study were parents of students of primary school age or Madrasah Ibtidaiyah (SD/MI). Data collection techniques through literature review by searching, tracing, reading, analyzing, and drawing conclusions from journals related to the research topic and then recording, processing, and analyzing them. The results of this study indicate that the role of parents is important in increasing children's interest in reading. Some of these roles include: a) being a role model and providing reading facilities; b) as a teacher and motivator; c) apply parenting and instill good values; and d) become a mentor or adviser. Some of these roles can be a factor in increasing children's interest in reading. Home is the best place to develop a child's interest in reading. One of the supports needed to increase children's interest in reading is the role of parents.